IDDF2022-ABS-0014 Prediction model of the recurrent risk of choledocholithiasis post ercp by biliary microbiota. (2nd September 2022) - Tan, Wenhui; Wu, Jiachuan; Chen, Ruiyan; Ye, Lifang; Yang, Xiaoqiao; Liang, Biao
Abstract : Background: To analyze the microbiotic characteristics of the bile duct in patients with recurrent choledocholithiasis post ERCP, and to establish a diagnostic model for identifying high-risk patients with early recurrence after ERCP. Methods: Next-generation sequencing was performed to investigate the bile duct microbiome of 4 early-relapse choledocholithiasis patients post ERCP in comparison with 15 patients without recurrence. The risk prediction model was constructed based on the microbiome characteristics. Results: The microbial composition in the bile duct at the initial operation was significantly lower than that in patients without recurrence, and the community function was different (P =0.039). Patients with early recurrence had a higher abundance of Clostridium, Laptotrichia and Neisseria in the biliary tract (P <0.05), while the relative abundance of Firmicutes was reduced (P <0.05). A random forest model was used to evaluate the value of biliary microbiologic indicators for early recurrence after ERCP, and it was found that the inclusion of predictive models of Fusobacterium, Paecilomycetes and Bacteroides have ideal diagnostic significance. Conclusions: The composition of the biliary microbiome has a good predictive value for the early recurrence of choledocholithiasis after ERCP. The strategy of analyzing the abundance of Fusobacterium combined with Pachybacterium and Bacteroides is of great clinical significance for the early assessment of the risk of recurrence of choledocholithiasis.